Calling Time Out in Doha: The Seiko Block Camera and Image Ethics. (July 2023) - Staton, David
In an effort to put more eyeballs on television sets, and in an attempt to reinvigorate a sport long beleaguered by doping scandals, recent questions surrounding female sponsorships, and a vanishing audience, the International Association of Athletic Federations unveiled a new camera designed by Seiko during the September 2019 World Championships held in Doha, Quatar. The idea was to add to an immersive experience, offering unparalleled views of sprinters at the moment they exploded from the starting blocks. Like many things during the Doha meet, the effort became an ending to a bad joke. Rather than getting to the heart of the event, the camera's focus was a bit lower; the Seiko angle became known derisively as the crotch shot. After objections by two female German sprinters the positioning of the camera angle (specifically what would be shown when) was reconsidered, reframed, and essentially retired. Control of the body, including how it is observed, and the closely related idea of the control of one's image are bound by certain ethical dimensions, particularly when that control is violated or profited from by outside parties. This paper interrogates how those concerns may be ameliorated by embracing an ethics of care.